Problemy i dylematy etyczne badań biomedycznych w kontekście realizacji projektu „Bionet” - Łaska-Formejster, Alicja (Acta Universitatis Lodziensis. Folia Sociologica, 2012)
Modern medicine is becoming more and more successful in the field of biomedical research, including clinical trials, and that is why a discussion concerning ethical, legal and social issues is necessary. The international perspective in this discussion plays an important role in this process, because dilemmas and expectations towards it are becoming more and more important and decisions which are taken have international range. The discussion which is going to fulfill these expectations was started by partners of 6th Framework Programme BIONET on Ethical Covernance of Biological and Biomedical Research: Chinese – European Co-operation. A wider perspective on this issue and specific standpoints of representatives from scientific circles from China and Europe presented in this article are just a part of a multinational debate on problems and dilemmas present in planning, managing and implementing biomedical and biological research. However opinions and statements presented here can prove the importance of these problems and their inevitability. While debating on challenges which the scientific circle has to face, both European and Chinese partners were trying to formulate standards in realization of projects and biomedical scientific research. It was widely discussed which conditions of planning, managing, implementing and conducting research should be fulfilled, in order that these scientific processes, which are realized within national and international range, would be conducted more effectively, safely and with respect for good standards of science and ethics.